2010
DOI: 10.1007/s11071-010-9783-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of a new electro-vibro-impact system

Abstract: A variety of nonlinear dynamic responses for a new electro-vibro-impact system is presented, with indication of chaotic behavior. By mathematical modeling of the physical system, an insight is obtained to the global system dynamics. The modeling has established a good correlation with experimental data, and hence can be used as a numerical tool to optimize the system dynamics. In particular, with respect to impact forces and progression rate, may then be achieved with minimal computational cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 37 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…Those models are inspired by a vibro-impact drifting oscillator studied by Pavlovskaia et al [18]. Experimental verification [19][20][21] and dynamic response analysis of such systems [22][23] have been investigated in order to carry out the best performance conditions, including the system stability and maximum progression rate. For capsule endoscopy applications, the system abilities for moving forwards and backwards are required.…”
Section: Introductionmentioning
confidence: 99%
“…Those models are inspired by a vibro-impact drifting oscillator studied by Pavlovskaia et al [18]. Experimental verification [19][20][21] and dynamic response analysis of such systems [22][23] have been investigated in order to carry out the best performance conditions, including the system stability and maximum progression rate. For capsule endoscopy applications, the system abilities for moving forwards and backwards are required.…”
Section: Introductionmentioning
confidence: 99%
“…Multistability has been observed in a broad range of engineering applications [7][8][9][10][11][12], and in some cases the coexisting stable solutions appear to be 'hidden', due to the complex structure of the basins of attraction [13]. In [14], the authors investigated the case of an impact oscillator with dry friction.…”
Section: Introductionmentioning
confidence: 99%
“…In [8], multistability was observed in a bilinear oscillator close to grazing, and the occurrence of coexisting attractors was manifested in an experimental investigation that revealed discontinuous transitions from one orbit to another via boundary crisis. The case of an electro-vibro-impact system was considered in [10], where the authors studied a broad range of dynamical scenarios with coexisting periodic and chaotic solutions. More recently, hidden coexisting oscillations were investigated in a drilling system [3], which were identified as a possible cause of harmful vibrations in the drill strings.…”
Section: Introductionmentioning
confidence: 99%
“…Such progression is sometimes referred to as a drift in the literature, which has received considerable attention in the past in the context of engineering applications, see e.g. [12][13][14][15]. In [12], the dynamics of a piecewise-linear drifting oscillator was studied and the analysis revealed that the largest drift was achieved when the system response switches from periodic to chaotic, originating from a cascade of period-doubling bifurcations.…”
Section: Introductionmentioning
confidence: 99%
“…Luo and co-workers [13] considered a two-degrees-of-freedom plastic impact oscillator with a frictional slider, and the largest progression was found when the system operates under period-1, multi-impact motion. Ho et al [14] studied the dynamic response of a electro-vibro-impact drifting system, and the highest progression rates and impact force of the system were achieved when periodic trajectories of the system occur. A novel drifting oscillator for analysis and prediction of percussive drilling was proposed by Depouhon et al in [15].…”
Section: Introductionmentioning
confidence: 99%